J.G. Ballard : landscapes of tomorrow - Brown, Richard, 1954-; Duffy, Christopher, 1977-; Stainforth, Elizabeth, 1986- (Dialogue (Brill Rodopi (Firm)), 2016)
An innovative volume of interdisciplinary essays on the significant British writer J.G. Ballard (1930-2009), exploring the physical, cultural and intertextual landscapes in several key novels with a central focus on The Atrocity Exhibition (1970), one of the most challenging texts in contemporary literature. Contributors include established critics of Ballard alongside newcomers. Different spatial concepts underpin the essays, from the landscapes of Ballard's youth in Shanghai and his life in suburban London, to nuclear testing spaces and outer space exploration. Figurative locations typical of Ballard's work are explored, including the beach, the motorway, the high-rise and the shopping mall. Textual spaces are explored through Ballard's affiliation with modernist literary forms, including surrealist prose writing and collage, and poetic romanticism.